Posterior suture annuloplasty for functional tricuspid regurgitation - Tchantchaleishvili, Vakhtang; Rajab, Taufiek K.; Cohn, Lawrence H. (Annals of Cardiothoracic Surgery; Vol 6, No 3 (May 31, 2017): Tricuspid Valve Surgery, 2017)
Functional tricuspid regurgitation (TR) is primarily caused by enlargement of the tricuspid annulus due to right ventricular dilation, frequently secondary to left sided valvular disease. Early techniques for the treatment of functional TR were introduced by Jerome Kay in 1965 and Norberto DeVega in 1972. Modified suture annuloplasty is a modification of DeVega’s semicircular purse string technique, however, it is based on Kay’s principle of obliteration of the posterior segment of the annulus only. While ring annuloplasty is the procedure of choice for severe functional TR, posterior suture annuloplasty is a technically simpler option for patients with moderate functional TR.